Mediastinitis: mortality rate comparing single-stage surgical approach and preconditioning of wound - Gib,Marcelo Curcio (2013)
OBJECTIVE: This study aims to compare hospital mortality rate of surgical debridement followed by primary wound closure versus surgical debridement with closure after preconditioning of the wound. METHODS: A historical cohort of 43 patients with postoperative mediastinitis type III and IV between 2000 and 2008. The diagnosis of mediastinitis was based on physical examination and laboratory tests. Patients were divided into two groups: patients who received the protocol of preconditioning of the wound (Group 2) and those who did not (Group 1). RESULTS: Of the 43 patients, 15 received the protocol and were assigned to Group 2, and 28 patients to Group 1. Myocardial revascularisation was the surgical intervention most affected by infection, accounting for 69.8% of patients in Group 1 and 64.3% in Group 2.Staphylococcus aureus was the predominant pathogen, accounting for 58.1% of all cases, 50% in Group 1 and 73.3% in Group 2. Hospital mortality rate was 42.9% in Group 1 and 20% in Group 2 (P=1.86), with relative risk of 2.14 and CI [0.714-6.043]. Among the 28 (65.1%) patients who underwent single-stage surgical approach, 12 (27.9%) underwent primary wound closure with irrigation, seven (16.3%) only primary closure, six (14%) omental flap, and three (7%) pectoralis muscle flap. CONCLUSION: Due to the lack of established guidelines, the choice of the surgical approach is based largely on low-level evidence references. Preconditioning of the wound appears to lead to a reduction in mortality in these patients, being a good surgical option.